Stabilization of complexes of redox-active guanidino-functionalized aromatic compounds (GFAs) by hydrogen-bonding - Krämer, Christoph; Wild, Ute; Hübner, Olaf; Neuhäuser, Christiane; Kaifer, Elisabeth; Himmel, Hans-Jörg (Australian journal of chemistry, 2014)
The guanidino-functionalized 1,2,4,5-tetrakis(N,N′-diisopropylguanidino)benzene could act as a redox-active switch, and reversibly forms hydrogen-bond aggregates upon two-electron oxidation. Herein the influence of hydrogen bonding on the structure and electronic properties of the first transition metal complexes of the neutral and oxidized compound are studied. Reaction with CuCl2 leads by coupled redox- and coordination processes to a dinuclear CuII complex of the dicationic guanidine, in which CuCl2- counterions are locked through strong hydrogen-bonds in positions above and below the C6 ring plane. The electronic situation in the electronic ground and excited states of this complex were analysed by quantum chemical calculations.
Gesehen am 25.09.2020